MEMBANGUN JIWA MANDIRI DAN KREATIF DALAM KEWIRAUSAHAAN BAGI ANGGOTA KOPERASI BUMI MANDIRI SEJAHTERA DI KELURAHAN PASIR KALIKI KECAMATAN CIMAHI UTARA - Adiputra, I Gede; Calvin; Budiman, Juan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
ABSTRACT The development of the creative economy cannot be separated from the young generation as a repository of creativity. Namely with creative ideas that can open up entrepreneurship and help the government in its efforts to reduce the unemployment rate in Indonesia. The more young people who want to enter the world of entrepreneurship, the more productivity will be generated which will have an impact on national economic development. Creative and innovative abilities are the basis for an entrepreneurial spirit to achieve success. An entrepreneurial spirit can encourage an independent, creative and innovative mentality, responsibility and not giving up easily when starting a business. The objectives of this PKM activity are as follows: a) As a form of counseling and motivating the community to be able to improve their abilities to support their abilities in the future, b) partner communities can train their mentality and creativity in entrepreneurship and entrepreneurship, c) Providing provisions for partners about the benefits of entrepreneurship. The problems faced are (1) entrepreneurial management has not been implemented optimally (2) good packaging has not been provided for the products being marketed and (3) labeling has not been provided to introduce the products. It can be concluded that: the implementation of service activities is in accordance with the plans that have been made and is running smoothly. Participants who take part in activities are more than the specified minimum number. This training provides participants with additional knowledge and understanding regarding creativity, innovation, independence, promotion and marketing as well as the importance of packaging and labeling. ABSTRAK Perkembangan ekonomi kreatif tidak lepas dari generasi muda sebagai gudang kreatifitas. Yaitu dengan ide kreatifnya yang dapat membuka wirausaha serta ikut membantu pemerintah dalam upaya mengurangi tingkat pengangguran di Indonesia. Semakin banyak anak muda yang mau terjun ke dunia wirausaha, semakin banyak juga produktifitas yang dihasilkan yang akan berdampak pada perkembangan ekonomi nasional. Kemampuan yang kreatif dan inovatif yang dijadikan dasar jiwa kewirausahaan untuk mencapai kesuksesan. Jiwa entrepreneur dapat mendorong mental yang mandiri, kreatif dan inovatif, bertanggung jawab serta tidak mudah menyerah ketika memulai usaha. Tujuan dari kegiatan PKM ini adalah sebagai berikut : a)Sebagai bentuk penyuluhan dan memotivasi masyarakat agar mampu meningkatkan kemampuan untuk menunjang kemampuannya di masa yang akan datang, b) masyarakat mitra dapat melatih mental dan kreatifitas dalam kewirausahaan dan entrepreneurship, c) Memberikan bekal bagi mitra tentang manfaat dari kewirausahaan. Permasalahan yang dihadapi adalah (1) belum maksimalnya manajemen wirausaha yang dilakukan (2) belum diberikan kemasan yang baik pada produk yang dipasarkan dan (3) belum diberikan labelling untuk mengenalkan produknya. Dapat disimpulkan bahwa:pelaksanaan kegiatan pengabdian sesuai dengan rencana yang telah dibuat dan berlangsung dengan lancar. Peserta yang mengikuti kegiatan lebih dari jumlah minimal yang ditetapkan. Pelatihan ini memberikan tambahan pengetahuan dan pemahaman peserta mengenai Kreativitas, inovatif, kemandirian, promosi dan pemasaran serta pentingnya kemasan dan labeling.